Vietnam INGO Directory 2008 (VUFO-NGO resource centre, 2008)
The document sought to be a resource providing information about the work organizations were conducting in the country, which activities they were involved in, and where they were working. This overall aim is still to: increase knowledge, in Vietnam and overseas, about INGOs working in Vietnam; and help foster communication among INGOs, the Government of Vietnam, local groups, organizations and associations, and other international and local agencies.